eLearning for health system leadership and management capacity building: a protocol for a systematic review - Car, Lorainne Tudor (2018)
Introduction: Health leadership and management capacity are essential for health system strengthening and for attaining universal health coverage by optimising the existing human, technological and financial resources. However, in health systems, health leadership and management training is not widely available. The use of information technology for education (ie, eLearning) could help address this training gap by enabling flexible, efficient and scalable health leadership and management training. We present a protocol for a systematic review on the effectiveness of eLearning for health leadership and management capacity building in improving health system outcomes. Methodology and analysis: We will follow the Cochrane Collaboration methodology. We will search for experimental studies focused on the use of any type of eLearning modality for health management and leadership capacity building in all types of health workforce cadres. The primary outcomes of interest will be health outcomes, financial risk protection and user satisfaction. In addition, secondary outcomes of interest include the attainment of health system objectives of improved equity, efficiency, effectiveness and responsiveness. We will search relevant databases of published and grey literature as well as clinical trials registries from 1990 onwards without language restrictions. Two review authors will screen references, extract data and perform risk of bias assessment independently. Contingent on the heterogeneity of the collated literature, we will perform either a meta-analysis or a narrative synthesis of the collated data. Ethics and dissemination: The systematic review will aim to inform policy makers, investors, health professionals, technologists and educators about the existing evidence, potential gaps in literature and the impact of eLearning for health leadership and management capacity building on health system outcomes. We will disseminate the review findings by publishing it as a peer-reviewed journal manuscript and conference abstracts.